2021
DOI: 10.1108/jkm-03-2020-0212
|View full text |Cite
|
Sign up to set email alerts
|

Comprehending a knowledge framework as a source of dynamic capabilities in IJVs through PLS-SEM

Abstract: Purpose This study aims to investigate the relationship among knowledge transfer enablers, knowledge transfer process, absorptive capacity and innovation performance in the context of Indian international joint ventures (IJVs). These elements are woven with the thread of dynamic capabilities theory (DCT) into an integrated framework. Design/methodology/approach Data analysis is conducted on a quantitative survey of 196 IJVs with partial least squares structural equation modeling as the statistical technique.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 78 publications
(70 reference statements)
0
20
0
Order By: Relevance
“…Meta-analytical studies have shown that organizational and managerial dynamic competencies are inevitable for a firm's innovativeness and sustainability (Lee and Kelley, 2008). Numerous researchers across the globe have emphasized the role of technical ability, strategic agility, cultural cognizance and structural flexibility as knowledge management enablers and innovation fostering agents (Aggarwal and Kapoor, 2020; Ashtiani, 2014; Borges et al , 2019; Dyer and Singh, 1998; Gim and Cheah, 2020; Goh, 2002; Huang and Chiu, 2020; Kapoor and Aggarwal, 2021; Karidou, 2008; Lemon and Sahota, 2004; Rhodes et al , 2008; Schilke et al , 2018; Shams et al , 2020). Thus, these four competencies are explicated below for further conceptualization.…”
Section: Constructs Explicationmentioning
confidence: 99%
See 4 more Smart Citations
“…Meta-analytical studies have shown that organizational and managerial dynamic competencies are inevitable for a firm's innovativeness and sustainability (Lee and Kelley, 2008). Numerous researchers across the globe have emphasized the role of technical ability, strategic agility, cultural cognizance and structural flexibility as knowledge management enablers and innovation fostering agents (Aggarwal and Kapoor, 2020; Ashtiani, 2014; Borges et al , 2019; Dyer and Singh, 1998; Gim and Cheah, 2020; Goh, 2002; Huang and Chiu, 2020; Kapoor and Aggarwal, 2021; Karidou, 2008; Lemon and Sahota, 2004; Rhodes et al , 2008; Schilke et al , 2018; Shams et al , 2020). Thus, these four competencies are explicated below for further conceptualization.…”
Section: Constructs Explicationmentioning
confidence: 99%
“…After organizational strategies, organizational culture is another crucial element in determining the learning, performance and sustainability of the firm (Goh, 2002; Kapoor and Aggarwal, 2021; Montreuil et al , 2020; Rhodes et al , 2008). Thus, this study has adopted cultural cognizance as the second dynamic capability (DC) or competency.…”
Section: Constructs Explicationmentioning
confidence: 99%
See 3 more Smart Citations